Legal Foundations of Economic Inequality in the Time Loop of Law and Economics Movement - Sanjeet Singh (Human Rights in the Global South (HRGS), 2023)
The role of law in breeding economic inequality has gone unnoticed for an extended period, however, is yet to be explored. To state and elaborate the problem, while capitalism has been considered to potentially contribute to the ongoing inequality trends in the world, there needs to be more literature on how the legal order in term of bolstering capitalism and economic inequalities are enlaced. The research problem is in regards to the extention of choice of legal structure undergirding capitalism correlate with economic inequality. As a limitation, this correlation should not be understood causally, as other underlying potential factors perpetuating economic inequality must exist. This article undertakes to fill the gap by utilizing epistemological and multidisciplinary approaches from the theories and practices of law and economics. Applying semiotic interpretation systems in forming arguments and drawing conclusions in doctrinal legal research. Various views enabled through the findings because both law and economics are partly subjective and irrational, which reshape the meanings. It founds that capitalism as a legal order is established to trace Economic inequality's legal roots. Therefore, appalling economic inequalities can co-exist with formal legal equality. Laws can reshape societies, but they serve capital, even when the movement of law and economics is at crossroads.